Hawa Nafsu Manusia dalam Perspektif Islam : Pengaruh terhadap Perilaku - Raihansyah Athallah; Muhammad Auliaurrasyidin; Afriza Medica Syahputra; M. Sukma Darmawan (Reflection : Islamic Education Journal, 2025)
Lust is a fundamental element in shaping human behavior. As an emotional and biological impulse, lust influences a variety of individual actions, both consciously and unconsciously. This study aims to explore the impact of lust on human behavior from a social, psychological, and moral perspective. With a qualitative approach, the study involves in-depth literature analysis as well as structured interviews with purposively selected respondents. The results of the study show that lust has a major impact on individual decision-making, social interaction, and moral tendencies. The ability to control lust can improve the quality of positive behavior, while failure to control it often leads to destructive behavior, such as aggression or abuse of authority. The study highlights the importance of character education and strengthening spiritual values to help individuals manage lust effectively to reduce the impact of .